Is there a short-run case for protectionism? Trade policy and the business cycle - Mario Larch; Wolfgang Lechthaler (Kiel Institute for the World Economy (IfW), 2011)
Recently, the world economy has seen its greatest down turn since World War II. Although not as bad as during the Great Depression, there was still a worrisome increase in protectionist measures, in an attempt to mitigate the economic downturn. Protectionism can have many different faces. It can come in the form of Buy-American clauses of stimulus packages, as an increase in trade barriers or tariffs, or as an increase in export subsidies. In this paper, we show that none of these measures constitutes an effective response to economic downturns. Although Buy-American clauses and export subsidies stimulate output in the short run, they are less effective than general government spending impulses. Raising tariffs or trade barriers even decreases output.
Keywords: E13; E60; F11; F12; F13; 330; Business cycle policy; Protectionism; Buy-American; Tariffs; Export subsidies; Protektionismus; Konjunktur; Konjunkturpolitik; Wirkungsanalyse; Vergleich; Dynamisches Modell; Theorie